Pembelajaran Menulis Cerpen Dengan Menggunakan Strategi Generative: Penelitian Eksperimen pada Siswa Kelas X SMA Negeri 1 Kelekar - Mulnapisa, Mulnapisa; Nuzulia, Dian; Murniviyanti, Liza (Institut Teknologi Pendidikan Indonesia, 2022)
This study aims to determine whether the generative strategy is effective On the ability to write short stories in class X SMA Negeri 1 Kelekar. This study uses a quantitative method with one research variable using an experimental model and data collection techniques carried out in this study using tests and documentation. In this case, this study found that there was an increase in the average value of the learning test using a generative strategy, namely, 46.96 to 86.3 then the generative learning strategy that the researcher applied in learning to write short stories was said to be effective where the researcher conducted a t-test and got the t result. count of 34.2 and t-table of 2.00 means that t count is greater than t table then Ha is accepted and Ho is rejected.